Potential-dependent reconstruction kinetics probed by HER on Au(111) electrodes. (1st July 2020) - Hermann, Johannes M.; Abdelrahman, Areeg; Jacob, Timo; Kibler, Ludwig A.
Abstract: The electrocatalytic hydrogen evolution reaction (HER) is employed to monitor the kinetics of potential-induced surface reconstruction of Au(111) in contact with either 0.1 M H2 SO4 or 0.1 M HClO4 in the temperature range between 17 and 25 °C. An apparent activation energy varying between 0.6 and 0.7 eV is found for the reconstruction process at 20 °C in the potential range between −0.1 and −0.7 V vs. saturated mercury-mercurous sulfate electrode (MSE). The rate constant of the first-order formation kinetics shows an exponential dependence on electrode potential and decreases with more negative potentials. The potential-dependence is associated with an increase in bond strength for Au surface atoms with increasing negative excess charge. Specific adsorption of anions hinders surface reconstruction at potentials close to the potential of zero charge, while the presence of carbon monoxide causes a significant enhancement of the rate for potential-induced Au(111) reconstruction. Graphical abstract: Image 1 Highlights: The hydrogen evolution reaction (HER) is used as structure-sensitive probe. Au(111) surface reconstruction rate decreases for more negative potentials. First-order kinetics is observed for potential-induced surface reconstruction. The activation energy ranges from 0.6 to 0.73 eV. Adsorption of carbon monoxide enhances surface reconstruction rate.